Strain specific differences in vitamin D3 response: impact on gut homeostasis - Schreiber, Laura; Ghimire, Sakhila; Hiergeist, Andreas; Renner, Kathrin; Althammer, Michael; Babl, Nathalie; Peuker, Alice; Schoenhammer, Gabriele; Hippe, Katrin; Gessner, Andre; Albrecht, Christin; Pielmeier, Fransziska; et al. (Frontiers in Immunology, 2024)
Vitamin D3 regulates a variety of biological processes irrespective of its well-known importance for calcium metabolism. Epidemiological and animal studies indicate a role in immune regulation, intestinal barrier function and microbiome diversity. Here, we analyzed the impact of different vitamin D3-containing diets on C57BL/6 and BALB/c mice, with a particular focus on gut homeostasis and also investigated effects on immune cells in vitro. Weak regulatory effects were detected on murine T cells. By trend, the active vitamin D3 metabolite 1,25-dihydroxyvitamin D3 suppressed IFN, GM-CSF and IL-10 cytokine secretion in T cells of C57BL/6 but not BALB/c mice, respectively. Using different2 vitamin D3-fortified diets, we found a tissue-specific enrichment of mainly CD11b+ myeloid cells but not T cells in both mouse strains e.g. in spleen and Peyer's Patches. Mucin Reg3γ and Batf expression, as well as important proteins for gut homeostasis, were significantly suppressed in the small intestine of C57BL76 but not BALB/c mice fed with a high-vitamin D3 containing diet. Differences between both mouse stains were not completely explained by differences in vitamin D3 receptor expression which was strongly expressed in epithelial cells of both strains. Finally, we analyzed gut microbiome and again an impact of vitamin D3 was detected in C57BL76 but not BALB/c. Our data suggest strainspecific differences in vitamin D3 responsiveness under steady state conditions which may have important implications when choosing a murine disease model to study vitamin D3 effects.